The Increase of Tapah fish (Wallago leeri) With Different Probiotic (Multi Cell) Doses on Growth and Survival - Fuad Muhamad Afandi; Usman M.Tang; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT                The research was conducted from October to November at UPT laboratory in the departement of aquaculture, faculty of fisheries and marine, university of riau. The purpose of this research was to determine the effect of proper probiotic on the growth and survival of tilapia (Wallago leeri). The research method is using a completely randomized design (CRD) experimental method with 1 factor consisting of 5 levels of treatment and 3 replications (15 units).The treatments used were P1 = 0 mL / m3, P2 = 3 mL / m3, P3 = 5 mL / m3, P4 = 7 mL / m3, P5 = 9 mL / m3. The best treatment for 40 days of maintenance was found in P3 with an absolute weight growth of 45.88 g, a daily growth rate of 2.06% / g, and an absolute length of 3.79 cm.  Keywords: Tapah fish (Wallago leeri), Probiotic